Corporate strategy for PT Tira Austenite - Satyawan, David S. (Animo Repository, 1999)
PT. Tira Austenite was founded in April 1974 as a venture between Johnny Santoso, a mechanical engineer and entrepreneur, and PT. Tigaraksa, a reputable trading company established in 1919. The company activities are divided into three sectors: Trading and Distribution • Manufacturing and Contract Manufacturing and Construction. The trading division of the company represents as either sole agent, distribution or license holder a long list of principals internationally renown in their fields such as Messer Griesheim, the oldest principals, Assab and The Lincoln Electric Company. Engineers, who make up 20% of the staff, are continuously supporting customers by advising on new products and techniques from the various principals. PT. Tira Austenites manufacturing division is as dynamic as their other divisions. Through PT. Alpha Austenite, a fully owned subsidiary, PT. Tira Austenite manufacturers a range of products for Indonesian industry. These products include moulds, dies, non ferrous castings, industrial parts and welding electrodes. In 1997, the Asian financial crisis spread out started from Thailand to Korea and Indonesia. PT. Tira was not excluding from the affect of the financial crisis. The growth of sales slowed down. The company incurred loss from the first of its operation for almost 23 years. The loss is mostly caused by foreign exchange loss. Rupiah have been depreciating as low as Rp. 17,000 against US dollars. The company, then, took some preliminary strategic actions such as organization restricting, debt restructuring, and improving its credit policies. However, the company should act more than use a reactivate strategy. What the company is doing now is merely a reaction to cope with the financial crisis. The company should think further to anticipate global competition. Global competition is almost there. Within 5 years ahead, Indonesian must open her market to foreign companies. This means competition will be getting stiffer than before. Next strategy is to build a breakthrough in trading business in Indonesian. In order to win more market share, PT Tira should develop new way of doing business in trading. The company is to establish One-Stop Shopping of industrial part. To support this planning, there are many preparation to be done such as virtual integration with suppliers to get more lenient credit policies, getting the right distributor, and preparing the most complete catalog in the country, etc. By implementing these two strategies, the company will be able to enhance its performance and gain more market share. Finally, the company will generate more revenue and profit, which is the bottom line of every business, and increase the value of the company.